(untitled) (Práxis Educativa, 2025)
The adoption of Generative Artificial Intelligence (GAI) tools, such as ChatGPT, is transforming higher education by reshaping access to and the generation of knowledge. These technologies offer opportunities to personalize learning and improve efficiency, but they also raise ethical challenges related to reliability, privacy, and academic integrity. Given the limited student training on the ethical use of GAI, this study presents the design, implementation, and evaluation of a workshop aimed at promoting responsible use of ChatGPT among students. A total of 140 students participated in the workshop. The results show high satisfaction and a strong interest in continuing to learn about the various uses of GAI. In conclusion, it is essential to foster critical reflection on these tools in order to integrate them ethically and responsibly into the university environment. Keywords: Artificial intelligence. ChatGPT. Workshop.